Perception of Prospective Teachers towards Four-Year Integrated Teacher Education Programme - Gupta, Dr. Pragya (Voices of Teachers and Teacher Educators, 2021)
Despite having the importance of 21st century skills (OECD, 2018), therefore, global perspective-oriented training of prospective teachers has been a decisive issue not only in India but overseas also. Ergo, the paradigm of teacher training in India has recently been shifted to integrated model (blending between content, pedagogy and technology) of teacher education followed by different models like horizontal integration (B.A. B.Ed. & B.Sc. B.Ed.) and vertical integration (M.A. B.Ed. & M.Sc. B.Ed.) for preparing committed, responsible and professional teachers to fulfil the needs and aspirations of the society and nation (NCTE, 2014). But nowadays it has become a debatable issue for ascertaining the effectiveness of the integrated model of teacher education programme to produce the best professionals. Therefore, this study has been focused to assess the perception of prospective teachers towards the Four-year Integrated Teacher Education Programme (ITEP). In the study, 93 prospective teachers of final year of four-year ITEP (B.A. B.Ed. - 48 & B.Sc. B.Ed. - 45) were selected through purposive sampling technique. The investigator used self-made tool for data collection. Qualitative analysis was used to analyse the data. The results reveal that prospective teachers’ perceptions towards ITEP are favourable to prepare professionals in the teaching profession by adopting the Technological Pedagogical Content Knowledge (TPCK) framework; helpful to qualify the necessary exams like CTET and STET. But some critical points are needed to rethink the reforms in the structure of ITEP, like bridging the gap between undergraduate and postgraduate level teacher education programmes, to reduce the credits load, coordination between liberal and education departments and true integration between theory, practice and technology. The findings of the study are expected to encourage the scholarly attention and critical reflections on the effects of different models on the professional competencies of prospective teachers. Possible educational implications and policy outcomes are outlined.